2017
DOI: 10.1101/237198
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Measurement of the mapping between intracranial EEG and fMRI recordings in the human brain

Abstract: (150 non-technical)There are considerable gaps in our understanding of the relationship between human brain activity measured at different temporal and spatial scales by intracranial electroencephalography and fMRI. By comparing individual features and summary descriptions of intracranial EEG activity we determined which best predict fMRI changes in the sensorimotor cortex in two brain states: at rest and during motor performance. We also then examine the specificity of this relationship to spatial colocalisat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…This finding was further corroborated by studying correlations between methods. In line with results obtained in simultaneous fMRI-ECoG recordings in animals (Logothetis et al, 2001; Niessing et al, 2005; Magri et al, 2012) as well as in human (Carmichael et al, 2017), we observed positive correlations between fMRI and high-frequency ECoG activity and negative correlations with low-frequency ECoG. We also observed negative correlations between EEG α band-power and BOLD in parietal, occipital and rolandic areas in line with previous reports on simultaneous recordings (Laufs et al, 2003; Moosmann et al, 2003; Ritter et al, 2009; Scheeringa et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding was further corroborated by studying correlations between methods. In line with results obtained in simultaneous fMRI-ECoG recordings in animals (Logothetis et al, 2001; Niessing et al, 2005; Magri et al, 2012) as well as in human (Carmichael et al, 2017), we observed positive correlations between fMRI and high-frequency ECoG activity and negative correlations with low-frequency ECoG. We also observed negative correlations between EEG α band-power and BOLD in parietal, occipital and rolandic areas in line with previous reports on simultaneous recordings (Laufs et al, 2003; Moosmann et al, 2003; Ritter et al, 2009; Scheeringa et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies in humans have used simultaneous fMRI–EEG recordings, including Laufs et al (2003); Moosmann et al (2003); Ritter and Villringer (2006); Scheeringa et al (2008); Ritter et al (2009); Scheeringa et al (2011, 2016). Simultaneous fMRI–ECoG recordings are only available in animals (Logothetis et al, 2001; Niessing et al, 2005; Magri et al, 2012) with a recent exception in human (Carmichael et al, 2017). Most human studies have relied instead on a common task (Mukamel et al, 2005; Nir et al, 2007; Hermes et al, 2012; Winawer et al, 2013; Harvey et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This finding was further corroborated by studying correlations between methods. In line with results obtained in simultaneous fMRI-ECoG recordings in animals (Logothetis et al, 2001;Magri et al, 2012;Niessing et al, 2005) as well as in human (Carmichael et al, 2017), we observed positive correlations between fMRI and highfrequency ECoG activity and negative correlations with lowfrequency ECoG. We also observed negative correlations between EEG α band-power and BOLD in parietal, occipital and rolandic areas in line with previous reports on simultaneous recordings (Laufs et al, 2003;Moosmann et al, 2003;Ritter et al, 2009;Scheeringa et al, 2009).…”
Section: Discussionsupporting
confidence: 92%
“…Simultaneous fMRI-EEG recordings in human have been performed in Laufs et al (2003); Moosmann et al (2003); Ritter et al (2009); Ritter and Villringer (2006); Scheeringa et al (2008Scheeringa et al ( , 2011Scheeringa et al ( , 2016. Simultaneous fMRI-ECoG recordings are only available in animals (Logothetis et al, 2001;Magri et al, 2012;Niessing et al, 2005) with a recent exception in human (Carmichael et al, 2017). Most human studies have relied instead on a common task (Harvey et al, 2013;Hermes et al, 2012;Mukamel et al, 2005;Nir et al, 2007;Winawer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the activity level of neuronal activity declines after seizures (known as post ictal depression), which is related to the pathological evolution of ion currents ( Panayiotopoulos, 2010 ). Another motivation includes the relationship between energy metabolism due to neuronal activity (caused by ion dynamics) and their level of demand for energy as observed in haemodynamic responses ( Rosa et al., 2011 ; Carmichael et al., 2017 ).…”
Section: Validation Analyses Using Simulated Datamentioning
confidence: 99%